Penyuluhan Hak-Hak Anak Sebagai Upaya Pemenuhan SDGs Di Yayasan Al Kamilah - Nurmasari Situmeang; Syahrul Salam; Rizky Hikmawan; Nurfarah Nidatya (AMMA : Jurnal Pengabdian Masyarakat, 2023)
In the 21st century there are still many cases of violation of children's rights which are quite concerning. Apart from economic demands, this problem arises due to the lack of knowledge about children's rights. Yet these rights are protected both nationally and internationally. Not to mention the implementation of the Sustainable Development Goals (SDGs), which consist of 17 global goals that also encourage the fulfillment of children's rights. Therefore counseling on children's rights that is carried out at the Yayasan Al Kamilah is one of the means to prepare children to know their rights. So that in the end they are able to implement these rights in various fields. In addition, an understanding of children's rights within the framework of the SDGs is also expected to be able to protect oneself well from various threats of violations of children's rights, such as violence and exploitation.